Exploring activist perspectives on Indigenous-settler solidarity in Toronto’s food sovereignty movement - Taliya Seidman-Wright; Sarah Rotz (Canadian Food Studies)
While food movements have increasingly taken up the framework of Indigenous food sovereignty in their work, settler food activists continue to define food systems on stolen lands. In this article, we explore whether and how food activists in Toronto are building solidarity with Indigenous peoples and movements in their work. Drawing on semi-structured interviews with food activists and content analysis of Toronto food organizations, we identify three main themes: (un)learning, relationship-building, and systemic constraints and visions for the future. Our findings reveal that many settler food activists are engaging in (un)learning processes, building decolonizing relationships, and supporting greater Indigenous leadership at their organizations. However, participants’ solidarity-building efforts are in the minority among food organizations more broadly, and there is significant work to be done to prioritize Indigenous struggles for land and sovereignty in food movement work. Further, NGO structure and function, corporatized and donor-centric funding models, and settler colonialism more broadly, significantly constrain the capacities of food organizations to align with Indigenous goals and visions. We argue that settler food activists have a responsibility to more deeply consider the role of food activism in upholding and challenging settler colonialism, to let go of settler claims to authority over food and knowledge systems on stolen lands, and to advocate for deeper systemic changes that redistribute power and resources to Indigenous peoples and Indigenous-led initiatives.